PENINGKATAN PENDAPATAN UMKM KERAJINAN PERAK MELALUI PERLUASAN JARINGAN PEMASARAN DAN PENGEMBANGAN DESAIN - Wardani, Dewi Kusuma; Mulyanto, Mulyanto (MIIPS, 2008)
Activity location " To Increase of Earnings of UMKM Silver Through Extension of Network Marketing and Development Desain" in Sub-Province Mount Kidul region , this matter pursuant to consideration that this region is including area hit by earthquake disaster on 27 May 2006. Congeniality of crafting of silver is crafting and made accessories with elementary materials of silver.Â UMKM face main problem, that is they only accept just making fare fee which its it him very determined by pemesan/ [both/ second] modal.Masalah owner that UMKM capital deficiency to produce [by] xself. While third problem, there is no UMKM owning trade merk / effort. So that [all] consumer more is recognizing [of] entrepreneur trade mark which in fact sell that UMKM product than recognizing UMKM which exactly its maker.Â Target of this activity that is improve earnings [of] UMKM [crafting/ diligence] [of] silver, passing extension [of] marketing network and product desain development. Result of this activity : UMKM more inovatif in yielding silver product , can make finance note and look for market alone without its irrespective [of] investor from Kotagede.